Geometric design method of fan blades - Baidabekov, Auyez (Рroblems of engineering and professional education, 2023)
The article the new method of designing with use of biquadratic transformation allows to receive various classes channel surfaces and to define the equation of family of cross-section of a considered surface that facilitates the further geometrical calculations on the computer.